Bioadsorbents for removal of microplastics from water ecosystems: a review - Patrick Mulindwa; Job S. Kasule; Florence Nantaba; John Wasswa; Antonio Jose Expósito (International Journal of Sustainable Engineering)
Microplastics (MPs) present a pressing environmental concern, posing formidable challenges to their effective elimination from water systems. Bioadsorbents offer a promising, eco-friendly, and cost-effective alternative to traditional removal methods. This review analyzes 206 research papers (2016-January 2024) to explore recent advances in bioadsorbent design and application for microplastic removal. We examine the sources and ecological impacts of MPs, then delve into the most studied bioadsorbents: biochar (51.9%), biomass-derived activated carbon (7.4%), synthetic sponges/aerogels (25.9%), and graphene-based materials (14.8%). The review critically analyzes factors influencing MP adsorption by these materials, including MP type and size, adsorbent properties, and experimental conditions. Reported removal efficiencies ranged from 31% to 100%, with polystyrene (52%) being the most common test polymer. Finally, the intricate mechanisms of MP-bioadsorbent interaction are discussed. We highlight key challenges and future research directions for optimising and scaling up bioadsorbent-based MP removal, acknowledging the early stage of this promising and sustainable approach.